Islamic Education Interventions in Children: Study Using the Al-Qur'an Approach - Mahyudin Ritonga; Apri Wardana Ritonga; Hasnil Oktavera; Ayu Desrani (JIE (Journal of Islamic Education), 2024)
This study aims to explore the intervention in the education of Islam in children using the approach of the verses of the Qur'an. The author uses a library research method that refers to literary sources as research data. Research data comes from the Al-Qur'an and Hadith as primary sources. At the same time, secondary sources are obtained from relevant articles and books. The collected data was then analyzed using content analysis techniques with the following steps: determining the problem, developing a framework for thinking, developing methodological tools, data analysis, and data interpretation. The results show that intervention in Islamic education using a Qur'an and Hadith-based approach can provide a strong foundation in shaping Islamic morality, ethics, and personality in children through various educational methods such as equality, cultivation, care, counsel, and punishment. Combining formal and informal education based on Islamic teachings can create a holistic academic environment for children's spiritual and intellectual development. This research contributes to enriching insights on implementing Islamic education in children through a more targeted and measured approach to using the Qur'an and Hadith as the primary sources in Islamic Education. Its practical implications lead to the development of more effective educational strategies to shape the Islamic character of the younger generation as a supply in the face of the ever-evolving challenges of the times.